How do Humans Overcome Individual Computational Limitations by Working Together?. Issue 1 (19th January 2023) - Vélez, Natalia; Christian, Brian; Hardy, Mathew; Thompson, Bill D.; Griffiths, Thomas L.
Abstract: Since the cognitive revolution, psychologists have developed formal theories of cognition by thinking about the mind as a computer. However, this metaphor is typically applied to individual minds. Humans rarely think alone; compared to other animals, humans are curiously dependent on stores of culturally transmitted skills and knowledge, and we are particularly good at collaborating with others. Rather than picturing the human mind as an isolated computer, we can imagine each mind as a node in a vast distributed system. Viewing human cognition through the lens of distributed systems motivates new questions about how humans share computation, when it makes sense to do so, and how we can build institutions to facilitate collaboration.